A necessary reflection on the skill solving clinical problems - Jorge Luis Losada Guerra; Elena Vicenta Hernández Navarro; Miguel Salvat Quesada; Juana María Remedios González; José Omar Losada Hernández (Centro Provincial de Información de Ciencias Médicas, 2018)
The development of skills related to clinical problems occupies a central site in the teaching-learning process of medical education, due to its special meaning in the general doctor professional performance. Due to the absence of this skill in the curriculum of the medicine career, this reflection study was carried out with the objective of supporting its incorporation to the skills system of the clinical method in the Cuban medical education. On the other hand, the skill in question was defined and its functional invariants were determined; that when being part of a methodological procedure, facilitate their integration to the system of teaching-learning methods to be used in the different forms of organization of the subjects that integrate the main discipline of the study plan D.